The Qualiflex Method For The Insurance Company Selection Problem - IÅŸik, AyÅŸegÃ¼l TuÅŸ; Adali, Esra AytaÃ§ (European Scientific Journal, ESJ, 2016)
Insurance is a tool for the process of protecting the people against the uncertainty and the loss of their life and property. This process is operated by an insurance company under a contract between insurance holder and insurance company. The contract may be signed for life, automobile, house etc. and the coverage of the contract may change from insurance company to company. So the selection of the most appropriate insurance company is not easy task. This selection may be handled as a MCDM (Multi Criteria Decision Making) problem. MCDM problems refer to make a decision for the alternatives characterized by multiple, usually conflicting, criteria. There are several methods for solving MCDM problems. In this paper, QUALIFLEX (QUALItative FLEXible) method, one of the MCDM methods, is applied to the insurance company selection problem. This method is based on the evaluation of all possible rankings (permutations) of alternatives in terms of concordance and discordance indices. The insurance company alternatives are ranked by this method and finally the results are discussed.